Hegelian Macroeconomics : The Dialectics of Global Imbalances - Monga, Celestin (World Bank, Washington, DC, 2014)
Traditional narratives of external imbalances have focused on the analysis of national accounts, trade flows, and financial flows. They have generated two opposing views of the current situation of the world economy: on one side, a prudent, if not pessimistic view considers large imbalances as evidence of problems with the international monetary and financial system, and symptoms of domestic distortions (mainly in the United States and China). On the other side, a relaxed, if not optimistic view suggests that global imbalances are not anomalies but simply the predictable outcome of a world with increasingly globalized financial flows in search of the right mix of risks and returns. The former view prescribes that the two largest countries in the world rebalance their economies to avoid the potentially painful cost of disruption and adjustment. The latter contends that global imbalances will be corrected through time by the normal functioning of market forces. This paper offers a critical analysis of these competing explanations of the United States-China imbalances and suggests a way of reconciling them. Starting with an exploration of the accounting frameworks that underpin any discussion of current account deficits and surpluses, the paper argues that China and the United States have become economically so interdependent that fears of any abrupt change in their current Nash equilibrium situation may be exaggerated. The paper also uses Hegel s parable of the development of self-consciousness to explain the dynamics between the two countries. Hegel may not have been a great philosopher of history but his analysis of lordship and bondage (also known as the master-slave dynamics) provides a good framework for analyzing the dialectics of recognition and acknowledgement that currently characterizes the macroeconomic relationships between the United States and China.